2015
DOI: 10.1177/0956797615617778
|View full text |Cite
|
Sign up to set email alerts
|

The Critical Importance of Retrieval—and Spacing—for Learning

Abstract: We examined the impact of repeated testing and repeated studying on long-term learning. In Experiment 1, we replicated Karpicke and Roediger's (2008) influential results showing that once information can be recalled, repeated testing on that information enhances learning, whereas restudying that information does not. We then examined whether the apparent ineffectiveness of restudying might be attributable to the spacing differences between items that were inherent in the between-subjects design employed by Kar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 21 publications
1
35
1
Order By: Relevance
“…The contrast of our findings with these other studies suggests that it is important to embed active learning exercises in lectures as low‐stakes formative assessments throughout the entire term. This idea is consistent with studies that have shown a large positive effect of repeated testing on student performance (Butler and Roediger, ; Karpicke and Roediger, ; Soderstrom et al, ), including in anatomy contexts (Logan et al, ; Dobson and Linderholm, ).…”
Section: Discussionsupporting
confidence: 88%
“…The contrast of our findings with these other studies suggests that it is important to embed active learning exercises in lectures as low‐stakes formative assessments throughout the entire term. This idea is consistent with studies that have shown a large positive effect of repeated testing on student performance (Butler and Roediger, ; Karpicke and Roediger, ; Soderstrom et al, ), including in anatomy contexts (Logan et al, ; Dobson and Linderholm, ).…”
Section: Discussionsupporting
confidence: 88%
“…Completing examinations as a group only, without having completed an individual portion first, does not allow students to determine and reflect on their own answer before discussing their reasoning with the group (Löfgren and Lundahl, ; Zimbardo et al, ). As a result, the repeated nature of the examination protocol in the current investigation may have resulted in greater improvements due to the benefits of repeated testing (Karpicke and Roediger, ; Gilley and Clarkston, ; Soderstrom et al, ). Compared to similar two‐stage collaborative examination protocols, the magnitude of score improvements here is consistent with previously reported score improvements (Gilley and Clarkston, ; Knierim et al, ; Rivaz et al, ; Green et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…When SenseCam photographs are periodically shown to memory‐impaired patients to help them remember recent events, the accessibility of these memory traces may be progressively strengthened through the well‐documented memory‐enhancing effects of spaced retrieval practice . It is also possible, if not likely, that the details of the event memories will be altered to some degree by each viewing of the photographs.…”
Section: Research In Clinical Contextsmentioning
confidence: 99%
“…When SenseCam photographs are periodically shown to memory-impaired patients to help them remember recent events, the accessibility of these memory traces may be progressively strengthened through the well-documented memory-enhancing effects of spaced retrieval practice. [45][46][47] It is also possible, if not likely, that the details of the event memories will be altered to some degree by each viewing of the photographs. Reminder cues are thought to return stored memories to a labile state in which they are briefly amenable to updating-and distortionbefore reconsolidation mechanisms act to stabilize the trace.…”
Section: Figure 2 a Comparison Of Autobiographical Recall In Patientmentioning
confidence: 99%